Degumming, Dewaxing and Deacidification of Rice Bran Oil‐Hexane Miscella Using Ceramic Membrane: Pilot Plant Study. (27th April 2014) - Roy, Biswajit; Dey, Surajit; Sahoo, Ganesh C.; Roy, Somendra N.; Bandyopadhyay, Sibdas
Abstract: An indigenously developed low‐cost clay‐alumina‐based ceramic microfiltration membrane of 19‐channel configuration has been evaluated for degumming, dewaxing and deacidification of rice bran oil (RBO) miscella having different oil contents at pilot scale. Rice bran wax and soap particles in miscella will aggregate with changes in temperature. This suggests a technique for their effective separation. Low‐temperature cross‐flow membrane filtration was used for single‐stage degumming‐dewaxing and showed 70 % and 80 % removal of acetone insoluble residue from two RBO miscella samples, respectively. Color reduction was 50 %, and oryzanol retention was 70 %. NaOH was used for deacidification in a 10 % excess of that required based on the free fatty acid content in oil. This reduced free fatty acids to 0.2 %. Operating for 10 h with a 0.7 bar trans‐membrane pressure, permeate fluxes of 15 and 8 L/m 2 hr were obtained for the degumming‐dewaxing and deacidification operations, respectively. The process has advantages, such as high micronutrient content (1.56 % oryzanol) and negligible oil loss (2.6 %). Moreover, ceramic membrane processing of RBO miscella could be an effective pre‐treatment step with respect to micronutrient enrichment, elimination of heating, neutral oil recovery and a viable option for solvent separation.